Nematodes infest winter-active chironomids in Minnesota trout streams - Hannah Bodmer; Corrie Nyquist (CHIRONOMUS Journal of Chironomidae Research, 2022)
We present preliminary findings of the effects of nematode infestation on winter-active chironomid biology, and how short-term temperature spikes could affect host-parasite interactions. Results are limited but indicate nematodes may infest winter-active chironomid communities and significantly affect host chironomid biology. Further research on winter-active insects should include investigations into nematode parasitism to better understand how climate change will affect chironomid survival at the population and community level.